2016
DOI: 10.1111/ggi.12756
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for disability progression among Japanese long‐term care service users: A 3‐year prospective cohort study

Abstract: The findings of the present study show that memory deterioration is a risk factor for disability progression. Also, grip strength might be a risk factor with consideration of chronic conditions. The cause-effect relationship of those factors and disability progression would be a future challenging issue. Geriatr Gerontol Int 2017; 17: 568-574.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In our previous report [ 4 ],36 out of 181 patients (19.9%) with a mean age of 68.1 ± 9.7 years (who were younger than the patients generally seen in actual clinical practice), experienced cardiac death or a HF readmission during the 2 years after discharge. Additionally, another of our previous studies in the elderly with care needs demonstrated that > 25% of the participants experienced disability progression during the 3 years observation [ 25 ]. Based on these preliminary observations, we determined that 2 years of follow-up for FLAGSHIP was sufficient to observe study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous report [ 4 ],36 out of 181 patients (19.9%) with a mean age of 68.1 ± 9.7 years (who were younger than the patients generally seen in actual clinical practice), experienced cardiac death or a HF readmission during the 2 years after discharge. Additionally, another of our previous studies in the elderly with care needs demonstrated that > 25% of the participants experienced disability progression during the 3 years observation [ 25 ]. Based on these preliminary observations, we determined that 2 years of follow-up for FLAGSHIP was sufficient to observe study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This was categorized into two groups: “support level 1–2 or care level 1–2” ( n = 92) and “care level 3–5” ( n = 109), as certified by the Japanese public long‐term care insurance system. This system has seven eligibility levels, including support levels 1–2 and care levels 1–5 (Kamiya, Adachi, Sasou, Suzuki, & Yamada, 2017). This study used medical record data from home‐visit dental treatment conducted at the request of patients and caregivers, so the duration of the observation period varied greatly from patient to patient.…”
Section: Study Population and Methodologymentioning
confidence: 99%
“…The participants sat with the wrist in a neutral position and the elbow flexed at 90° [ 22 ]. Two trials were completed for each hand and the strongest value was used for the analysis [ 23 ]. In our previous study, grip strength was an independent associated factor of slow gait in older women aged 75 years and above [ 6 ].…”
Section: Methodsmentioning
confidence: 99%